A within-person comparison of the subjective effects of higher vs. lower-potency cannabis. (1st November 2020) - Okey, Sarah A.; Meier, Madeline H.
Highlights: Cannabis concentrates have higher average THC concentration than marijuana flower. Concentrates were rated as producing less positive subjective effects than flower. Minimal negative subjective effects were reported for both concentrates and flower. Subjective effects might not explain why cannabis users use cannabis concentrates. Abstract: Background: Cannabis concentrates have much higher concentrations of THC than marijuana (flower) and are quickly gaining popularity in the United States. One hypothesis is that use of higher-THC cannabis (concentrates) might result in greater intoxication and more severe acute negative effects than lower-THC cannabis (marijuana), but few studies have compared the subjective effects of concentrates and marijuana. Methods: Current (past-year) cannabis users were recruited online to complete a survey about their cannabis use. Cannabis users who reported using both marijuana and concentrates (n = 574) answered questions about the subjective effects of marijuana and, subsequently, the subjective effects of concentrates. Subjective effects were obtained for the following domains: affect, cognitive function, psychotic-like experiences, physiological effects, and reduced consciousness. Results: Participants reported using marijuana between 5–6 times per week and concentrates slightly more than once per month. Within-person comparisons of the subjective effects of marijuana and concentrates showed that marijuana was rated as producing greater overall positive effects (Marijuana: M = 5.6, Concentrates: M = 4.5; Cohen's d = 0.75, paired t (561) = 14.67, p < .001), including greater positive affect and enhanced cognitive function. Negative effects of both marijuana and concentrates were minimal. Marijuana was selected over concentrates as the 'preferred type' of cannabis by 77.5 % of participants. Conclusions: The main difference in the subjective effects of marijuana and concentrates is in terms of their positive effects, with marijuana producing greater positive effects than concentrates. Negative effects of marijuana and concentrates were small, suggesting that extreme negative effects are unlikely for regular cannabis users.